REDUCTION OF AQUEOUS TRANSITION METAL SPECIES ON THE SURFACES OF FE(II)-CONTAINING OXIDES - White A.F.; Peterson M.L. (My University, 1996)
Experimental studies demonstrate that structural Fe(II) in magnetite and ilmenite heterogeneously reduce aqueous ferric, cupric, vanadate, and chromate ions at the oxide surfaces over a pH range of 1-7 at 25°C. For an aqueous transition metal m, such reactions are3[Fe2+>Fe3+2]O4(magneite) + 2/nm^ -> 4[Fe3+2]O3(maghemite) + Fe2+ + 2/nm^z-n and3[Fe2+Ti]O3 (ilmenite) + 2/nm^z -> Fe3+2Ti3O9(pseudorutile) + Fe2+ + 2/nm^z-n , where z is the valance state and n is the charge transfer number. The half cell potential range for solid state oxidation [Fe(II)] -> [Fe(III)] is -0.34 to -0.65 V, making structural Fe(II) a stronger reducing agent than aqueous Fe2+ (-0.77 V). Reduction rates for aqueous metal species are linear with time (up to 36 h), decrease with pH, and have rate constants between 0.1 and 3.3 x 10^1p>1. Iron is released to solution both from the above reactions and from dissolution of the oxide surface. In the presence of chromate, Fe2+ is oxidized homogeneously in solution to Fe3+.X-ray photoelectron spectroscopy (XPS) denotes a Fe(III) oxide surface containing reduced Cr(III) and V(IV) species. Magnetite and ilmenite electrode potentials are insensitive to increases in divalent transition metals including Zn(II), Co(II), Mn(II), and Ni(II) and reduced V(IV) and Cr(III) but exhibit a log-linear concentration-potential response to Fe(III) and Cu(II). Complex positive electrode responses occur with increasing Cr(VI) and V(V) concentrations. Potential dynamic scans indicate that the high oxidation potential of dichromate is capable of suppressing the cathodic reductive dissolution of magnetite. Oxide electrode potentials are determined by the Fe(II)Fe(III) composition of the oxide surface and respond to aqueous ion potentials which accelerate this oxidation process.Natural magnetite sands weathered under anoxic conditions are electrochemically reactive as demonstrated by rapid chromate reduction and the release of aqueous Fe(III) to experimental solution. In contrast, magnetite weathered under oxidizing vadose conditions show minimum reactivity toward chromate ions. The ability of Fe(II) oxides to reduce transition metals in soils and groundwaters will be strongly dependent on the redox environment.